Current status and trends in thalassemia burden across South, East and Southeast Asia, 1990–2021 a systematic analysis for the global burden of disease study 2021 - Shuning Zhang; Zhangjie Chen; Meihuan Chen; Hailong Huang (BMC Public Health)
Abstract Objective Thalassemia, an inherited hemoglobin synthesis disorder, imposes a significant health burden in Asian regions with high prevalence. Detailed patterns and trends of the disease across countries and territories within these regions remain underexplored. Our study focuses on the disease burden indices of thalassemia within the four GBD-defined Asian regions and the twenty-five included countries and territories. It provides insights into the gender-age distribution, temporal changes, and economic aspects of the thalassemia burden. Methods Data on thalassemia prevalence, incidence, mortality, and Disability-Adjusted Life Years (DALYs) were extracted from the Global Burden of Disease (GBD) 2021 study for South, East, Southeast, and high-income Asia regions, encompassing the relevant countries and territories from 1990 to 2021. The Average Annual Percent Change (AAPC) in age-standardized rates of thalassemia was determined to assess temporal trends. Age-gender cohort proportions were considered. The economic aspect of the disease burden and frontier analysis were evaluated using the GBD Socio-Demographic Index and Global Health Expenditure data. Results Southeast Asia exhibited notably high age-standardized mortality rate (ASMR), age-standardized prevalence rate (ASPR), and age-standardized DALYs rate among the four studied Asian regions in 2021. The East Asia region had recorded the highest age-standardized incidence rate (ASIR). A general decline in disease burden indices across the four regions from 1990 to 2021 was evident, with the exception of ASIR in Southeast Asia. The ASMR was highest among pediatric population under five years old, with a significant male preponderance. An unusual increase in ASMR was detected among females of childbearing age and the elderly within the studied region. Further analysis had identified six high-burden countries and territories, particularly those with low-middle Socio-Demographic Index (SDI) rankings and limited health expenditure. Conclusion Although the overall burden of thalassemia has decreased substantially, the disease burden was influenced by gender, age, geography, temporal trends, and economic factors in distinct manners. Based on the current SDI, many countries and regions still have greater improvement potential in the disease burden. There is a necessity for enhanced attention and resource allocation, particularly in low-middle and low SDI countries, with an emphasis on policies that promote early diagnosis and comprehensive care.